CONSORT for reporting randomized controlled trials in journal and conference abstracts: explanation and elaboration. - Hopewell, S; Clarke, M; Moher, D; Wager, E; Middleton, P; Altman, D; Schulz, K; CONSORT Group (2008)
Clear, transparent, and sufficiently detailed abstracts of conferences and journal articles related to randomized controlled trials (RCTs) are important, because readers often base their assessment of a trial solely on information in the abstract. Here, we extend the CONSORT (Consolidated Standards of Reporting Trials) Statement to develop a minimum list of essential items, which authors should consider when reporting the results of a RCT in any journal or conference abstract.